2021
DOI: 10.1186/s12865-021-00397-w
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps are present in the airways of ENaC-overexpressing mice with cystic fibrosis-like lung disease

Abstract: Background Neutrophils are key components of the exacerbated inflammation and tissue damage in cystic fibrosis (CF) airways. Neutrophil extracellular traps (NETs) trap and kill extracellular pathogens. While NETs are abundant in the airways of CF patients and have been hypothesized to contribute to lung damage in CF, the in vivo role of NETs remains controversial, partially due to lack of appropriate animal models. The goal of this study was to detect NETs and to further characterize neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…NETs in tissue samples have similarly been shown as extracellular DNA colocalized with neutrophil-derived proteins ( 49 ). NET remnants such as DNA and neutrophil-derived protein complexes (MPO-DNA; neutrophil elastase (NE)-DNA) and citrullinated histones can be determined by ELISA in fluid samples ( 50 , 51 ) or detected by flow cytometry ( 52 , 53 ) as indicators of NETosis.…”
Section: Introductionmentioning
confidence: 99%
“…NETs in tissue samples have similarly been shown as extracellular DNA colocalized with neutrophil-derived proteins ( 49 ). NET remnants such as DNA and neutrophil-derived protein complexes (MPO-DNA; neutrophil elastase (NE)-DNA) and citrullinated histones can be determined by ELISA in fluid samples ( 50 , 51 ) or detected by flow cytometry ( 52 , 53 ) as indicators of NETosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic [ 47 ], cardiac [ 48 ] and renal [ 49 ] fibrosis was also linked to NETs persistence. Recently, NETs were found in the lungs of a cystic fibrosis mouse model in the absence of bacterial infection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPO-DNA complexes were detected in the BALF of infected WT and Rgs10-/- mice following a published protocol ( 26 , 27 ) adapted to murine samples ( 28 ). BALFs were diluted 1:25 in PBS and were subsequently added to a high-binding 96-well ELISA microplate pretreated overnight at 4 °C with capture anti-MPO (1:200 RD Systems, Cat#: AF3667).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the abundant neutrophil infiltrates in infected airways of Rgs10-/-mice, we explored whether soluble markers of NETs are also increased in the lungs of PR8-infected Rgs10-/-mice. Cell-free BALF supernatants were collected from WT and Rgs10-/-mice at 0 and 5 dpi and the presence of NET-specific MPO-DNA complexes was assessed as previously (26)(27)(28). While there was no significant difference in the BALF MPO-DNA complexes level between WT and Rgs10-/-mice at 0 dpi, we found that there was a significant, 4-fold increase in the absorbance values in the BALFs of infected Rgs10-/-mice compared to their WT littermate controls (Figure 6A), indicating the enhanced release of NETs in infected airways of these animals.…”
Section: Rgs10 Deficiency Increases Neutrophil and Monocyte Recruitment Into The Airway During Iav Infectionmentioning
confidence: 99%